Kary i nagrody stosowane przez rodziców a samoocena młodzieży = Rewards and penalties used by parents and self-esteem of youth - Kuźmik, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Self-esteem is one of elementary needs of each individual. It can be also a precious resource, that allows self-realization. The main goal of research was to present relations between selfesteem and specific penalties and rewards. Analysis of answers granted by respondents in questionary shows significant meaning of positive reinforcments in shaping high self-esteem in tested group.
Keywords: kara; nagroda; rodzina; samoocena; poczucie własnej wartości; penalties; rewards; family; self-esteem